Using the activity-based costing (ABC) method to achieve the competitive advantage of the economic enterprise: a case study of the textile and processing enterprise TIFIB in Biskra - toumi, miloud; djehiche, youssera (Journal of Research in Finance and Accounting, 2022)
This study aims to highlight the role of the activity-based cost method in achieving the competitive advantage of the economic enterprise in light of the developments in its business environment. In order to achieve this goal, the analytical descriptive approach was relied on in the theoretical aspect, while in the practical aspect, we relied on a case study of the Textile and Equipment Corporation (TIFIB) in Biskra, through information, documents and information from its side. Contributes to achieving the competitive advantage of the economic institution by reducing the costs of its production operations, ie achieving the strategy of leadership in cost.